2018
DOI: 10.3168/jds.2017-14008
|View full text |Cite
|
Sign up to set email alerts
|

Preweaned heifer management on US dairy operations: Part II. Factors associated with colostrum quality and passive transfer status of dairy heifer calves

Abstract: Passive transfer of immunity is essential for the short- and long-term health of dairy calves. The objective of this study was to evaluate factors associated with colostrum quality and passive transfer status of US heifer calves. This study included 104 operations in 13 states that participated in the calf component of the National Animal Health Monitoring System's Dairy 2014 study. This 18-mo longitudinal study included 1,972 Holstein heifer calves from birth to weaning. Multivariable mixed linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
2
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 35 publications
8
74
2
12
Order By: Relevance
“…A total of 77.4% of samples had colostrum IgG level greater than 50 g/L. 46 Factors affecting colostrum quality and yield are reviewed next and methods for testing colostrum quality are discussed.…”
Section: Factors Associated With Colostrum Quality and Yieldmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 77.4% of samples had colostrum IgG level greater than 50 g/L. 46 Factors affecting colostrum quality and yield are reviewed next and methods for testing colostrum quality are discussed.…”
Section: Factors Associated With Colostrum Quality and Yieldmentioning
confidence: 99%
“…Most, but not all, studies report a tendency for older cows to produce higher-quality colostrum, presumably /because of older animals having had a longer period of exposure to farm-specific pathogens. 46,49,50 In a study by Shivley and colleagues, 46 colostrum from first and second lactation cows had similar colostrum quality (73.2 and 71.7 g/L of IgG), whereas colostrum from third lactation and older cows was of higher quality (83.3 g/L IgG). Producers should test and record the quality of all colostrum fed.…”
Section: Age Of Dammentioning
confidence: 99%
See 1 more Smart Citation
“…This percentage has decreased from a study conducted by Beam et al (2009), which reported 19.1% of heifer calves had FPT, as well as from 1991 to 1992, in which over 40% of calves had FPT (USDA, 1993). It appears that this number may be decreasing over time; however, it is important to note that the most recent large-scale studies (Beam et al, 2009;Shivley et al, 2018) were conducted either as a convenience study, due to less farms participating in the study than anticipated , or included only healthy heifer calves (Beam et al, 2009), whereas the USDA (1993) did not distinguish between healthy and unhealthy calves before blood collection. Therefore, although the most current rate of FPT is reported as 12.1%, it is likely that the true rate of FPT on North American dairy farms could be greater.…”
Section: Colostrum Feedingmentioning
confidence: 99%
“…At approximately 24 h after birth (Stott et al, 1979a), "gut closure" occurs, which is defined as "the cessation of absorption of macromolecules from the gut into blood in neonates" (Lecce and Morgan, 1962). Shivley et al (2018) found that serum IgG concentrations decreased by 0.32 mg/mL every hour following birth after colostrum feeding, and it is widely accepted that the absorption of IgG decreases in a linear trend as calves age (Stott et al, 1979a;Bush and Staley, 1980;Matte et al, 1982). However, Fischer et al (2018c) recently demonstrated a nonlinear trend in the absorption of IgG, with calves fed immediately after birth (0 h) having greater serum IgG concentrations compared with calves fed at 6 and 12 h after birth, which did not differ.…”
Section: Colostrum Feedingmentioning
confidence: 99%